Volumen 9 l Enero – Diciembre de 2021 - López Zemanate, Victor Hugo; Pérez Garzón, Carlos Andrés; Alzate Castrillón, María Camila; Andrade Montenegro, Gloria Fabiana; Valencia Banguera, Katty Dayanna; Portilla Parra, Sebastian; Camargo Rojas, José Arvey; Hernández Ávila, Emmer Antonio (Justicia y Derecho, 2021)
Volumen 9 l Enero – Diciembre de 2021